Spectacle of Music: Critical Essay on the Evolution of Music in North Sumatra - Merdy Roy Sunarya Togatorop; Muhammad Yusuf (Universitas Negeri Medan, 2023)
Music, as part of culture, is often seen as something that only plays a complementary role in life. In fact, if explored in depth, there are many things stored in the music, which are worthy of in-depth study. Music has deposits that describe the natural state of mind, environment, culture and existence of the owner of the music. In general, the essence of music is a sound engineering event. If it is related to sound, then it is enjoyed by hearing. However, in the archipelago in general, and Sumatra in particular, music has become something that is enjoyed by